Economic and Distributional Impacts of Free Trade Agreements : The Case of Indonesia - Cali, Massimiliano; Maliszewska, Maryla; Olekseyuk, Zoryana; Osorio-Rodarte, Israel (World Bank, Washington, DC, 2019)
As preferential trade agreements are growing in number and depth, assessment of their economic impacts has become more important to inform policy-makers facing a multitude of potential preferential trade agreements. This paper provides novel ex ante estimates of the impacts of two key preferential trade agreements currently negotiated by Indonesia, the largest economy in Southeast Asia. The paper then compares these estimates with those of other preferential trade agreements that Indonesia may negotiate in the future. To that end it, combines a dynamic, multi-country computable general equilibrium model and a microsimulation tool linking the macroeconomic results to household-level welfare. The results suggest that, among the preferential trade agreements considered, the European Union–Indonesia Comprehensive Economic Partnership Agreement (EU-CEPA) is expected to yield the largest gains for Indonesia in income, output, and exports. This result is due to a combination of large expected reductions in trade barriers and a high share of international trade between the partners. These macro effects translate into the highest expected income growth relative to the other preferential trade agreements at every point of the income distribution. However, the gains for the EU-CEPA are proportionately larger for richer households, unlike the other agreements considered. The regressive gains are mainly due to the increase in skill wage premia spurred by the additional demand for skill-intensive sectors, especially services.